Adventitious Root Characteristics of Some Assamica Tea Clones (Camellia sinensis L. Kuntz) - Taryono, Sriyanto Waluyo; Sholehan (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2014)
ABSTRACTTea is multiplied either through generative or vegetative propagation systems. Vegetative propagation is limited by several factors such as poor survival rate at nursery due to poor root formation of some clones and seasonal dependent rooting ability of cutting, however root system plays an important role in regulating of water uptake and absorb nutrient from the soil. Root formation was believed under genetically control, therefore the objective of this research is to characterize genetically the adventitious root of some tea clones. Seven clones were explored to study the adventitious root formation through the improvement of rooting media. The result showed that (1) improvement of root quality of tea through adding rooting media with plant growth regulators seemed difficult to be implemented, (2). Rooting of tea cutting is under genetic control, (3) effort to improve root quality of tea through breeding approach looked visible in the future.Keyword : assamica tea, root, characters